Blastocyst transfer is not associated with increased unfavorable obstetric and perinatal outcomes compared with cleavage-stage embryo transfer. (2nd November 2017) - Li, Wei; Xue, Xia; Zhao, Wanqiu; Ren, Anqi; Zhuo, Weiwei; Shi, Juanzi
Abstract: Background: Recent studies demonstrated controversial results of whether there are risks in fetal outcomes after blastocyst-stage embryos transfer (BT) compared with cleavage-stage embryos transfer (CT). Aims: To compare the implantation rates (IR), clinical pregnancy rates (cPR), birth rates (BR), gestational weeks, preterm birth rates, birth weights and low birth weight rates between CT and BT groups. Methods: A retrospective study of 1627 embryos transfer cycles was performed from May 2014 to April 2015. The cycles were divided into two groups according to transfer stage: CT on Day 3 ( n  = 798) and BT on Day 5 ( n  = 829). For the CT group, it must have surplus embryos and only surplus embryos developed to available blastocysts, the cleavage-stage embryos could be included. The clinical outcomes of two groups were analyzed. Results: The IR in CT group was lower than BT group (48.98% vs. 60.68%; p  < 0.01). There were no significant differences in the clinical pregnancy rate and birth rate between BT and CT groups. For singletons and twin deliveries, there were no significant differences in gestational weeks, preterm birth rates, birth weights and low birth weight rates between two groups. Conclusion: Blastocysts had higher implantation potential than cleavage-stage embryos. Extended embryo culture was not related to increased adverse obstetric and perinatal outcome.